THE PLACE AND SIGNIFICANCE OF FINE PAINTING IN FINE ARTS - Bakhtior Obidov (Social science and innovation, 2023)
In the article, in the art of painting lessons, students are taught to see and feel colors and to distinguish between subtle nuances in them, which in the future will create skills such as doing any work they start with aesthetic taste, using their whole being and skills. It is also said that painting teaches students to clearly see and feel beauty, but also to reflect it more vividly, and that visual art serves as an artistic tool in creating creative works.